Tools for using the International Rice Genebank to breed for climate-resilient varieties - McNally, Kenneth L.; Henry, Amelia (2023)
Traditional rice varieties have been critical for developing improved stress-tolerant rice varieties. Tools to analyze the genome sequences of traditional varieties are accelerating the identification and deployment of genes conferring climate change resilience